Computer simulation of unsteady flow in natural channels - Liongson, Leonardo Q. (1973)
A preliminary derivation of the continuity and momentum equation is done for a one-dimensional, unsteady open-flow in a natural channel. These equations are transformed into two characteristic equations whicha re valid along a certain so-called characteristic curves in the x-t plane. The steady flow equation is also obtained as a special case of unsteady flow equations. The steady flow equation is solved numerically using the step method and the result is taken as the initial condition of the steady flow. The characteristic equations are solved numerically by the methods of characteristics, subject to the upstream end condition imposed by the input hydrograph there and to the downstream end condition which is the flow rating curve at open control station or else just the condition of closed control station. These numerical algorithms are incorporated in a computer program that is tested with two main blocks of case problems, namely the Agus River problem and the problem of a hypothetical channel.
Thesis (M.S. in Hydraulic Engineering)--University of the Philippines, Diliman.
Keywords: Hydraulics -- Computer simulation; Channels (Hydraulic engineering) -- Philippines